Cooperative Approach: A Survey on Students’ Preferred Classroom Activities in Reading Classes at Thu Dau Mot University - Hong Thi Xuan Nguyen; Du Thanh Tran (Vietnam Journal of Education, 2021)
The Cooperative approach or Cooperative learning approach is defined as a model of group learning in which students are assigned to cooperate in teams for gaining a common purpose whereas they have to show their independence in completing sectional tasks. This learning style, to some extent, has been used in Reading classes at Thu Dau Mot University along with other methods for boosting students’ working motivation. From the mentioned premise, the paper investigated English-majored students’ favorable activities in Reading classrooms to clarify student’s learning motives as well as their willingness to work in group during the lessons. A survey questionnaire on selective activities was sent to the fourth–year English majors to measure the respondents’ attitudes. Accordingly, the paper focuses on the following aspects: (1) students’ attitudes towards reading skills, (2) their preferred classroom activities, and (3) their expected achievements from the course. Consequently, it is found out that there was a kind of intrinsic motivation among learners in the course, the students are interested in self-conducted activities, and that cooperative learning activities might foster students’ love for reading.